Diagnosis, Treatment, and Prevention Resources for Infectious Diseases in Sub-Saharan African Hospitals Caring for Children - Samiksha Tarun MD; Workeabeba Abebe MBBS; Maitry Mahida MPH; Lisa Saiman MD; Wilmot James PhD; Philip LaRussa MD; Lawrence R. Stanberry MD (SAGE Publishing, 2023)
Objective. The Children's Hospitals in Africa Mapping Project survey was developed and implemented to assess the readiness of hospitals in sub-Saharan African to respond to emergencies, epidemics, and pandemics affecting children. Methods. This sub-study analyzed 56 survey questions that characterized the hospitals and assessed resources for diagnosis, treatment, and prevention of community-acquired infections and healthcare-associated infections (HAIs). Results. Twenty-four sites were recruited and 20 (from 15 countries) completed the survey in 2018 to 2019. Overall, 90% to 100% of sites reported that diagnostic assays were available for malaria, tuberculosis, and HIV. Periodic shortages of antibiotics, antimalarial drugs, and vaccines were reported by 45%, 25%, and 20% of sites, respectively. Sites reported formal programs for infection prevention and control (79%), monitoring HAIs (17%), and antimicrobial stewardship (53%). Conclusions. Opportunities to improve care for hospitalized African children were identified. These included resources for HAI surveillance and antimicrobial stewardship which can facilitate epidemic and pandemic preparedness.